Small cell carcinoma of the rectum metastasizing to axillary lymph nodes: A case report - Özgen IŞIK; Ersin ÖZTÜRK; Eylem AKAR; Ömer Yerci; Tuncay YILMAZLAR (Turkish Journal of Gastroenterology, 2019)
-